A study of evaluation method for buffer material erosion in vertical in-hole emplacement - UDA, Toshiaki; KIKUCHI, Hirohito; EMORI, Minoru; HAYASHI, Daisuke; KIMURA, Shun (Journal of Nuclear Fuel Cycle and Environment, 2024)
In the vertical in-hole emplacement, using compacted bentonite blocks which is being considered for the geological disposal of high-level radioactive waste, there is concern that groundwater inflow into the disposal hole may result in the outflow of some of the buffer material. This phenomenon is anticipated to occur from emplacement of buffer material to completion of backfill material construction in the disposal tunnel. There are concern that the phenomenon may affect the function of the engineered barrier. This study attempted to construct a model for evaluating the erosion of buffer material that can be assessed from an engineering perspective in Japan's geological environments, using the erosion model proposed by SKB (Swedish Nuclear Fuel and Waste Management Company) as a reference. In the in-situ erosion tests using the test holes of the Horonobe URL (Underground Research Laboratory), we confirmed phenomena such as a decrease in groundwater flow over time and the cessation of buffer material erosion, which differ from the element tests based on constant flow conditions that form the basis of the erosion model. We gained an understanding of influencing factors from these phenomena, such as spring water quantity, water level differences between surrounding rock formations and disposal holes, water property, material properties, and conditions inside the disposal hole from these phenomena. From these findings, the erosion evaluation model of buffer material was presented based on the results of element tests at a control to constant water level. The main parameters of the erosion evaluation model were the water head difference inside and outside the disposal hole and the spring water quantity inside the disposal hole, which can be obtained in-situ, and also took into account the period of concerns about the erosion of the buffer material. The erosion evaluation model developed in this study was able to approach a more realistic evaluation compared to the erosion model. In additionally, the study showed the development methodology and challenges of the erosion evaluation model.